Effect of Bacillus subtilis JZXJ-7, a Strain Isolated from Shrimp Paste, on Colonic Function and Microbial Community in Mice Infected with Vibrio parahaemolyticus - ZHOU Kui, WANG Rundong, GONG Mengxue, MOU Jingyuan, DENG Yijia, LI Xuepeng, ZHANG Yuhao, LI Jianrong (Shipin Kexue)
The protective effect of Bacillus subtilis JZXJ-7 (JZXJ-7) on Vibrio parahaemolyticus (Vp) infected mice was investigated. Totally 28 male C57BL/6J mice were randomly divided into four groups: a Vp infection model group (infected with the standard virulence strain ATCC33847), two JZXJ-7 intervention groups (administered at low (106 CFU) and high (108 CFU) doses by gavage), and a control group. The control and model groups were administered with an equal volume of normal saline. Disease activity index (DAI), Vp load in the intestine tract (including the ileum, cecum, and colon), colonic pathological alterations, colonic cytokine contents, oxidative stress resistance, and changes in intestinal microbial community composition were detected in all groups. The results showed that the protective effect of JZXJ-7 was better at the high dose than at the low dose. High-dose JZXJ-7 significantly reduced the DAI and intestinal Vp load in Vp infected mice, alleviated inflammatory cell infiltration and collagen deposition, and increased the number of intestinal epithelial goblet cells (P < 0.05). Moreover, high-dose JZXJ-7 significantly inhibited cytokine-mediated inflammation, increased antioxidant enzyme activities and enhanced intestinal permeability. Furthermore, JZXJ-7 significantly increased (P < 0.05) intestinal microbial diversity, partially reversing intestinal flora disturbance, enriching Akkermansia, Bifidobacterium, Clostridium and other beneficial bacteria, and thus resulting in the restoration of intestinal microecological homeostasis. In summary, JZXJ-7 can effectively alleviate colonic pathological damage in Vp infected mice and maintain intestinal functions, and the underlying mechanism may be related to its regulatory effect on the intestinal microbiota.